Pengaruh Budaya Organisasi terhadap Kinerja Guru dengan Perilaku Kerja Inovatif sebagai Variabel Intervening (Studi pada Guru SLB Negeri Semarang) - Fabiana Silfi Priliantari; Edy Raharja (Faculty of Economics and Business | Universitas Diponegoro, 2022)
The purpose of this study was to determine the influence of Organizational Culture on teacher performance with innovative work behavior as an intervening variable for Semarang State SLB teachers. The population used was Semarang State SLB teachers, with a total sample of 70 teachers.Â The sample collection technique in this study is the Census technique. The data collection method used was distributing questionnaires by measuring the sample questionnaire using a Likert scale of five (5). The data analysis method uses Structural Equation Modeling (SEM) which is run with the SmartPLS software version 3.2.9.Â The results of this study indicate that organizational culture has a positive and significant effect on teacher performance. Organizational Culture has a positive and significant effect on Innovative Work Behavior. Innovative work behavior influences teacher performance. This research also shows that Innovative Work Behavior can be an Intervening variable on the influence between Organizational Culture and Teacher Performance